Awangardowy wnuk Leśmiana - Stankowska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The sketch discusses the “relations and interdependencies of impossibilities” connecting the discursive poetry of Bieńkowski with the lyrical poetics of Leśmian. This formula, coined by the author of Sprawy wyobraźni, perfectly expresses these kind of references that exceed just a simple juxtaposition of similarities in subject matters or poetical figures. In terms of this plane, there seem to be are more differences between the two poems than conceivable similarities. However, within the plane of creative philosophy, the awareness of the language status in modern poetry, the abiding concept of reality and the attitude towards civilizational and social transformations, the similarities are particularly striking. The avant-garde poet does not shun from employing early modernist individualistic, idealistic, regressive and aesthetic (formalistic) tendencies so characteristic for Leśmian. If Przyboś, as Łapiński put it, “rehabilitated” Leśmian’s programme, Bieńkowski makes the Przyboś’ programme back again more like Leśmian-like, creating a programme not so much avant-garde in character but rather a one that relates to decadent aspirations of modernism in its narrowest sense. Not surprisingly then, he makes the lyrics of the author of Łąka his particular tertium comparationis of the phenomena in Polish postwar poetry, linguistic poetry in particular. This way, unusual power of modernity of Leśmian poetry is testified and well proven.